The Role of Visual and Printed Media in Raising Awareness of Environmental Risks and Pollution (Eurasian Journal of Media and Communications, 2024)
Environmental issues are considered to be a substantial matter that the modern world is occupied with. This is due to the enormous development in the industrial field which lead to the development of environmental problems by affiliation. Which indicates the important role of media in spreading awareness among citizens about the environmental issues and risks with proposed solutions. The current study discusses pollution in Iraq, environmental issues and the importance of raising awareness of them, the role of media and its role of raising awareness of its environmental risks, the possible sorts of media used for raising awareness, as well as a hint of environmental media